AUDIT FEE, AUDITOR’S EXPERIENCE, AND EARNINGS MANAGEMENT: EVIDENCE FROM LISTED MANUFACTURING COMPANIES IN NIGERIA - Muhammed Kamaldeen Usman; Adeoluwa Victoria Adekanye (Malete Journal of Accounting and Finance)
Manipulation of financial statement has a great consequence on the economy as it could lead to the collapse of many manufacturing companies. This study examined the effects of audit fee and auditor’s experience on earnings management of listed manufacturing companies in Nigeria. In order to achieve this, Ex-post facto research design was utilized with the population consisting of seventy-six (76) listed manufacturing companies. Sixty-four (64) companies were chosen as the sample size using Krejcie and Morgan (1970) sample size determination table. Descriptive and inferential statistics were employed in the analysis of the data collected from the annual reports and accounts of the chosen companies for the period of five years (2013-2017). The study found out that audit fee has a significant negative effect on the level of earnings management of listed manufacturing companies in Nigeria at 5% significant level (t-value of -0.3409 with p-value of 0.001). However, auditor’s experience has no significant relationship with earnings management (t-value of -0.0021 with p-value 0.063). The study concluded that audit fee has a significant negative impact on earnings management of listed manufacturing companies in Nigeria, while auditor’s experience has no significant effect. Therefore, the study recommended that management should not have a fixed remuneration for external auditors. Rather, it should be reviewed periodically and that separate audit firms should be employed to provide non-audit services to a client’s firm.